Eyaluation of Damage Leyel in Glass-Fabric Reinforced Composite - Bełzowski, Andrzej (Engineering Transactions, 2005)
A method is proposed for evaluating the extent of damage in fibre-reinforced polymer composites. The available methods for monitoring fatigue degradation in such materials are critically discussed. Reported are the results of actual tests on a glass-epoxy laminate under cyclic bending. The relative changes in the bending strength were several times higher than those of the dynamic stiffness, total elastic energy of a cycle and phase shift. A relationship is put forward for calculating the level of damage allowing for the mean value and the standard deviation of residual strength. The analysis is enhanced by presenting microscopic images of the material structure. The proposed model was shown to give reliable estimates of durability and can be especially useful to validate the damage parameter determined by other methods.